The biology of insect chitinases and their roles at chitinous cuticles. - Rabadiya, D.; Behr, M. (Insect Biochemistry and Molecular Biology, 2024)
Chitin is one of the most prevalent biomaterials in the natural world. The chitin matrix formation and turnover involve several enzymes for chitin synthesis, maturation, and degradation. Sequencing of the Drosophila genome more than twenty years ago revealed that insect genomes contain a number of chitinases, but why insects need so many different chitinases was unclear. Here, we focus on insect GH18 family chitinases and discuss their participation in chitin matrix formation and degradation. We describe their variations in terms of temporal and spatial expression patterns, molecular function, and physiological consequences at chitinous cuticles. We further provide insight into the catalytic mechanisms by discussing chitinase protein domain structures, substrate binding, and enzymatic activities with respect to structural analysis of the enzymatic GH18 domain, substrate-binding cleft, and characteristic TIM-barrel structure.